British Creoles: Nationhood, Identity, and Romantic Geopolitics in Robert Southey's History of Brazil. (19th July 2019) - Fermanis, Porscha
Abstract: This essay considers the nationalist preoccupations underpinning Robert Southey's three-volume History of Brazil (1810–1819), maintaining that there are important links between his historiographical practices and his rethinking of British imperialism in relation to the challenges raised by the Peninsular War and Napoleonic France. It argues that Southey's rejection of many of the discourses associated with European encodings of the imperial frontier—such as climatic determinism, sentimental and stirring descriptions, and conquest narratives—forms part of the emergence of a new legitimatory style of British national historiography. While Southey deflates sublime or heroic tales of discovery and conquest, he nonetheless naturalizes the European experience in Brazil via a latent Anglocentric subtext, simultaneously co-opting the hegemonic tendencies of Spanish/Portuguese imperialism, and representing Britain as a benign colonial power divorced from the violence and cruelty associated with those regimes. As Southey's Brazilians progress towards independence from Portugal, they are invested with more refined moral sensibilities and peculiarly 'British' national qualities, making their drift towards emancipation a vindication of a superior British colonial culture. Southey thus uses Brazil as a complex geopolitical space with which to examine a number of his most pressing national concerns, including his fears regarding French imperialism, his residual support for anti-slavery and emancipatory movements, his faith in British expansionism and missionary interventionism, his understanding of the British national character, and his endorsement of new models of ethnic and civic nationalism pioneered in South America.